Serial measurements of neutrophil gelatinase-associated lipocalin: prognostic value in patients with ST-segment elevation myocardial infarction treated with a primary percutaneous coronary intervention. Issue 8 (December 2017) - Lim, Yeong-Min; Moon, Jae Youn; Min, Daniel; Kim, Sang-Hoon; Yang, Woo-In; Kim, Won-Jang; Sung, Jung-Hoon; Kim, In Jai; Lim, Sang-Wook; Cha, Dong-Hun
Abstract : Background: There are no previous data on serial changes in neutrophil gelatinase-associated lipocalin (NGAL) levels in ST-segment elevation myocardial infarction (STEMI) patients before and after a primary percutaneous coronary intervention (pPCI). The aim of the present study was to evaluate the prognostic value of serial NGAL measurements in patients with STEMI treated by pPCI. Materials and methods: We identified 169 STEMI patients who underwent pPCI within 12 h of symptom onset and had plasma NGAL measurements before (pre-NGAL) and 6 h after (post-NGAL) pPCI. The primary endpoint was 30-day all-cause mortality, including cardiac death, whereas the secondary endpoint was the change in NGAL levels from before to after pPCI. Results: The mean pre-NGAL and post-NGAL levels were 109.2±76.1 and 93.3±83.8 ng/ml, respectively. Thirty-day mortality occurred in 12 (7.1%) patients. In terms of changes in serial NGAL levels, post-NGAL levels were decreased in 132 (79%) patients. Patients with elevated post-NGAL levels showed increased mortality compared with patients with decreased post-NGAL levels ( P =0.005). Multivariate analyses indicated that old age and high post-NGAL levels were independent risk factors for 30-day mortality. Conclusion: In a large percentage of STEMI patients, plasma post-pPCI NGAL levels were decreased compared with pre-pPCI NGAL levels, even with the administration of potentially nephrotoxic contrast medium. Post-NGAL levels seemed to be superior to pre-NGAL levels for the prediction of 30-day mortality outcome.